Isolated Word Recognition Using Ergodic Hidden Markov Models and Genetic Algorithm - Nyoman Rizkha Emillia; Suyanto Suyanto; Warih Maharani (Universitas Ahmad Dahlan, 2012)
Speech to text was one of speech recognition applications which speech signal was processed, recognized and converted into a textual representation. Hidden Markov model (HMM) was the widely used method in speech recognition. However, the level of accuracy using HMM was strongly influenced by the optimalization of extraction process and modellling methods. Hence in this research, the use of genetic algorithm (GA) method to optimize the Ergodic HMM was tested. In Hybrid HMM-GA, GA was used to optimize the Baum-Welch method in the training process. It was useful to improve the accuracy of the recognition result which is produced by the HMM parameters that generate the low accuracy when the HMM are tested. Based on the research, the percentage increases the level of accuracy of 20% to 41%. Proved that the combination of GA in HMM method can gives more optimal results when compared with the HMM system that not combine with any method.